2022
DOI: 10.1002/solr.202200394
|View full text |Cite
|
Sign up to set email alerts
|

Codesigning Alloy Compositions of CdSeyTe1−y Absorbers and MgxZn1−xO Contacts to Increase Solar Cell Efficiency

Abstract: Thin‐film solar cells such as CdTe are a major commercial photovoltaic technology, with more than 25 GW installed worldwide and levelized costs of electricity competitive with fossil fuels. Further progress may result from integrating CdSeyTe1−y absorbers with MgxZn1−xO contacts, but the device efficiency is difficult to maximize due to coupled dependence on chemical composition of both alloys. Herein, a high‐throughput approach is demonstrated to codesign chemical compositions in alloyed MgxZn1−xO/CdSeyTe1−y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Finally, the co-design of the elemental compositions of the electron transport layer (ETL) and the absorber represents a new field, and its widespread application across various materials has not been widely explored. One of these few efforts was devoted to the codesign of alloy compositions of CdSe x Te 1_x (as an absorber material) and Mg y Zn 1-y O (as an ETL) [49]. In their experimental study, the authors revealed that the solar cell performance is a strongly coupled function of both x and y compositions.…”
Section: Codesign and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the co-design of the elemental compositions of the electron transport layer (ETL) and the absorber represents a new field, and its widespread application across various materials has not been widely explored. One of these few efforts was devoted to the codesign of alloy compositions of CdSe x Te 1_x (as an absorber material) and Mg y Zn 1-y O (as an ETL) [49]. In their experimental study, the authors revealed that the solar cell performance is a strongly coupled function of both x and y compositions.…”
Section: Codesign and Optimizationmentioning
confidence: 99%
“…In their experimental study, the authors revealed that the solar cell performance is a strongly coupled function of both x and y compositions. They achieved a PCE of up to 17.7% at specific atomic compositions (x = 0.04 and y = 0.18) [49]. As this field of research is advancing, a need for simulation studies is mandatory to investigate and evaluate new material systems and to provide design guidelines for the corresponding solar cells.…”
Section: Codesign and Optimizationmentioning
confidence: 99%